2017
DOI: 10.7567/jjap.56.06gn15
|View full text |Cite
|
Sign up to set email alerts
|

Development of magnetic-field-driven artificial cilium array with magnetic orientation in each cilium

Abstract: Artificial cilia actuated by an applied magnetic field have been developed. In our previous report, we demonstrated actuated cilia of a few millimeters scale, which were fabricated by cutting a magnetic elastomer sheet. The fabricated artificial cilia worked similarly to natural cilia; however, they had a much larger structure than natural ones, and showed difficulty for use in pumping systems in micro-total analysis systems (µTAS) fields. Thus, our goal is further miniaturization. In this study, we introduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…As we have already shown in previous researches, ciliary movement is asymmetric [15][16][17][18][19][20][21][22][23][24]. The stroke pattern of a natural cilium consists of 2 different strokes; the effective stroke and the recovery stroke.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…As we have already shown in previous researches, ciliary movement is asymmetric [15][16][17][18][19][20][21][22][23][24]. The stroke pattern of a natural cilium consists of 2 different strokes; the effective stroke and the recovery stroke.…”
Section: Introductionmentioning
confidence: 97%
“…If we could apply biomimicry structures of these natural cilia, they would be useful engineering tools. We utilized magnetic elastomer [7][8][9] to mimic the motion of flexible structures in natural cilia [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of artificial cilia consist of microactuators that are incorporated in silicone rubber pillars or plate‐like flexible structures in order to mimic the biological hair‐like design. Current actuation methods include electric fields, magnetic fields, vibrations, mechanical forces, or pressurized fluids . However, asymmetric motion remains the most challenging feature to mimic in artificial cilia systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we demonstrated a new 3D-printing system using magnetic particles for artificial cilia. Natural cilia are known as an effective fluidic device, and the motion of cilia has been researched to realize bio-mimic soft actuators [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Several studies on artificial cilia driven magnetically have been reported [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%